Managemen Pelayanan Kartu Tanda Penduduk Elektronik (E-KTP) pada Kantor Dinas Kependudukan dan Pencacatan Sipil Kabupaten Konawe - Rahmatyah, Sitti; Sarning, Suci (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine themanagement of the identity card service and the factors that influence themanagement of the identity card service at the Of ice of Population and Civil Registration of Konawe Regency. The research method with this research location was carried out at the Of ice of Population and Civil Registration located in Konawe Regency. The choice of theplace and location of the study was based on the reason that the researcher wantedto know the case of the eL ID card service at the agency. This type of qualitative research with data sources consisting of primary data and secondary data. There search informants consisted of the Head of Population Registration Service, Headof Population Administration Information Management, Staf and the public whouse the Electronic Identity Card service. Data collection techniques using observation and interview guidelines. Data analysis techniques include data reduction, data presentation and verification. The results of the study found that the service management systemfor the Electronic Identity Card is said to be quite good, it can be seen in the application of the e-KTP service shown by the employees in serving applicants in the formof service quality carried out from the process of preparing, implementing plans, coordinating and completing service activities as well as the influencing factors, namely organizational structure, employee performance and service system. And results to ensure the realization of the expectation of the Electronic Identity Cardissuance service.